Social construction of knowledge in synchronous text-based discussion during English language learning - Ira Mutiaraningrum; Arif Nugroho (Journal on English as a Foreign Language, 2020)
The uptake of remote learning during the COVID-19 pandemic was indispensable. Classroom activity, including English language learning, was shifted into remote learning. However, remote learning has not escaped the question regarding its role in students' knowledge construction in language learning. Thus, this study explores whether the social construction of knowledge occurs in the same-time synchronous text-based discussion during students' English language learning. It also investigates the phasesin which the social construction of knowledge present. Content analysis of the Interaction Analysis Model was used as the method to classify twenty-three Indonesian English as foreign language students' discourses in the synchronous text-based discussion. The transcripts from two threads in Google Classroom were sorted into the Interaction Analysis Model Phases to find out the percentage of each Phase's occurrence. Results indicate that the discourses showed the social construction of knowledge was developed by students and thereby pointed out the process of their cognitive thinking during their synchronous English language learning. This study suggests that the social construction of knowledge exists in synchronous text-based discussion with the most frequent postings categorized in Phase I.